Source Water Safety Investigating Unregulated Synthetic Organic Chemicals. Issue 8 (1st August 2014) - Williams, Gordon; Howe, Elaine; Owens‐Bennett, Emily; Hokanson, David; Trussell, Rhodes
Abstract : Analytical technology can detect synthetic organic chemicals at increasingly smaller concentrations in our environment. Water utilities must understand the significance and potential health implications of these compounds.